Eyebrow Incision and Supraorbital Craniotomy: craniopharingioma - Dinark Conceição Viana (Brazilian Society for Pediatric Neurosurgery, 2019)
A 6 year-old boy presented with progressive decrease of visual acuity in his left eye. Neurological examination revealed a left third nerve palsy. His ophthalmological assessment showed left amaurosis and right temporal hemianopia. Head magnetic resonance scans revealed a suprasellar parachiasmatic lesion causing compression of optic chiasm. The boy underwent a supraorbital craniotomy through a left eyebrow incision; gross total resection was achieved. Postoperatively, the patient was neurologically stable, with visual improvement and no additional neurological deficits. Pathology confirmed the diagnosis of craniopharyngioma.